Standard versus physiologic bone preparation in total knee arthroplasty and the effect on joint space opening. (November 2017) - Burkhart, Timothy A.; Herman, Benjamin V.; Perry, Kevin; Vandekerckhove, Pieter-Jan; Howard, James; Lanting, Brent
Abstract: Background: Total knee arthroplasty is an effective treatment for osteoarthritis. Restoration of physiologic varus alignment may restore the native soft tissue tension and improve outcomes. Methods: Six paired fresh-frozen knee specimens were used to perform total knee arthroplastys. The left and right sides of were randomly assigned to have either a physiologic alignment cut or a standard of care neutral alignment bony cut prior to the implantation. Loads of 100 and 200 N were applied at 0, 30, 60, and 90° of flexion and the magnitude of the medial and lateral compartment distraction was measured. The loads were applied with the knee specimen intact and post arthroplasty. Findings: The physiologic alignment had no difference between medial and lateral gaps at either load. With 100 N of load the physiologic alignment had a greater gap at 90° than at full extension while the standard alignment had significantly more gap at 60° of flexion than full extension. The physiologic alignment had a significantly greater gap with the implant compared to the intact condition at both loads. The standard alignment had no significant difference in overall gap between the implant and intact condition with any load. Interpretation: Although performing a physiologic aligned TKA resulted in medial-lateral soft tissue balance, the flexion gap was found to have greater magnitude than the intact knee. Notably, a neutral aligned TKA was found to be balanced, but also was found to recreate the intact knee flexion gaps. These results suggest that coronal plane stability can be achieved with physiologic alignment objectives, but the clinician needs to be aware of the potential to have greater laxity than the intact and neutral alignment surgical objectives. Highlights: Current total knee arthroplasty bone preparation methods may result in anatomical imbalances. Instability following a total knee arthroplasty is a common problem resulting in revision. Restoring physiologic varus may reinstate native soft tissue tension. Physiological preparation increases tissue release and leads to greater distraction.